Impairment of IFN-Gamma Response to Synthetic Peptides of Mycobacterium tuberculosis in a 7-Day Whole Blood Assay - Gideon, Hannah Priyadarshini (Public Library of Science, 2013)
Studies on Mycobacterium tuberculosis (MTB) antigens are of interest in order to improve vaccine efficacy and to define biomarkers for diagnosis and treatment monitoring. The methodologies used for these investigations differ greatly between laboratories and discordant results are common. The IFN-gamma response to two well characterized MTB antigens ESAT-6 and CFP-10, in the form of recombinant proteins and synthetic peptides, was evaluated in HIV-1 uninfected persons in both long-term (7 day) and 24 hour, commercially available QuantiFERON TB Gold in Tube (QFT-GIT), whole blood assays. Our findings showed differences in the IFN-gamma response between 24 hour and 7 day cultures, with recombinant proteins inducing a significantly higher response than the peptide pools in 7 day whole blood assays. The activity of peptides and recombinant proteins did not differ in 24 hour whole blood or peripheral blood mononuclear cell (PBMC) based assays, nor in the ELISpot assay. Further analysis by SELDI-TOF mass spectrometry showed that the peptides are degraded over the course of 7 days of incubation in whole blood whilst the recombinant proteins remain intact. This study therefore demonstrates that screening antigenic candidates as synthetic peptides in long-term whole blood assays may underestimate immunogenicity.